Glass-limited Yb/Er:NaLuF4 nanocrystals: reversible hexagonal-to-cubic phase transition and anti-counterfeiting. Issue 45 (25th October 2020) - Wang, Shaoxiong; Lin, Jidong; Li, Xiaoyan; Chen, Jiangkun; Yang, Changbin; Huang, Ping; Cheng, Yao; Chen, Daqin
Abstract : Yb/Er:NaLuF4 @glass with in situ reversible cubic-to-hexagonal phase transition on cyclic heat-treatment shows practical application in high-level anticounterfeiting. Abstract : The development of luminescent materials with concurrent tunable spectral profile and brightness is a great challenge to improve the security of the authentic items and shield against counterfeiting. Herein, we report the realization of in situ hexagonal-to-cubic phase transition of Yb/Er:NaLuF4 nanocrystals inside inorganic glass via simply modifying the heating (glass crystallization) temperature, leading to simultaneous control of upconversion emission color and intensity. Impressively, this peculiar phase transition process is reversible upon cyclic heating/cooling thermal-treatment and the accompanying repeatable upconversion emission behaviors are retained. It is experimentally demonstrated that multiple patterns visualized using screen-printing inks containing the investigated samples and the anti-counterfeiting prototypes are practically applicable by switching in situ glass crystallization temperatures. These findings show great promise of the designed lanthanide-doped NaLuF4 @glass nanocomposites in high-level anticounterfeiting applications and give new insights for the development of advanced optical materials.